Antifungal activity of neem (Azadirachta indica: Meliaceae) extracts against dermatophytes (2015)
In order to assess the antifungal activity of methanolic extracts from neem tree (Azadirachta indica A. Juss.), several bioassays were conducted following M38-A2 broth microdilution method on 14 isolates of the dermatophytes Trichophyton mentagrophytes, Trichophyton rubrum, Microsporum canis and Epidermophyton floccosum. Neem extracts were obtained through methanol-hexane partitioning of mature green leaves and seed oil. Furthermore, high performance liquid chromatography (HPLC) analyses were carried out to relate the chemical profile with their content of terpenoids, of widely known antifungal activity. The antimycotic Terbinafine served as a positive control. Results showed that there was total growth inhibition of the dermatophytes isolates at minimal inhibitory concentrations (MIC) between 50 μg/mL and 200 μg/mL for leaves extract, and between 625 μg/mL and 2500 μg/mL for seed oil extract. The MIC of positive control (Terbinafine) ranged between 0.0019 μg/mL and 0.0313 μg/mL. Both neem leaves and seed oil methanol extracts exhibited different chromatographic profiles by HPLC, which could explain the differences observed in their antifungal activity. This analysis revealed the possible presence of terpenoids in both extracts, which are known to have biological activity. The results of this research are a new report on the therapeutic potential of neem to the control of dermatophytosis. Actividad antifúngica de extractos de neem (Azadirachta indica: Meliaceae) sobre hongos dermatofitosSe determinó la actividad antifúngica de extractos metanólicos de la especie Azadirachta indica A. Juss. (Meliaceae), conocida comúnmente como neem, empleando el método de microdilución en caldo M38-A2 de referencia para hongos filamentosos y dermatofitos. Se evaluaron 14 aislamientos de los dermatofitos Trichophyton mentagrophytes, Trichophyton rubrum, Microsporum canis y Epidermophyton floccosum. Los extractos de neem fueron obtenidos mediante partición metanol-hexano a partir de aceite de semillas y hojas verdes maduras. Adicionalmente, se analizaron por cromatografía líquida de alta resolución (CLAR) con el fin de relacionar su perfil químico con el contenido de terpenoides, de conocida actividad antifúngica. Se empleó como control positivo el antimicótico Terbinafina. Los resultados mostraron inhibición total del crecimiento de los aislamientos de dermatofitos a concentraciones mínimas inhibitorias (CMI) entre 50 μg/mL y 200 μg/mL para el extracto de hojas y entre 625 μg/mL y 2500 μg/mL para el extracto de aceite de semillas. La CMI encontrada para el control positivo (Terbinafina) fluctuó entre 0,0078 μg/mL y 0,0313 μg/mL. Los extractos metanólicos de hojas y aceite de semillas de neem exhibieron diferentes perfiles cromatográficos en CLAR, lo cual podría explicar las diferencias observadas en su actividad antifúngica. Éste análisis químico reveló la posible presencia de compuestos terpenoides en ambos extractos, los cuales se conocen por su actividad biológica. Los resultados de esta investigación son un nuevo aporte sobre el potencial terapéutico del neem para el control de dermatofitosis.